Students’ Difficulties in Translating Idiomatic Expression from English into Indonesian - Dian Paramita Ayuningtyas; Muhimatul Ifadah; Siti Aimah (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research is about the difficulties in translating idiomatic expressions. It is aimed to find out about how students translate the idiomatic expressions, and the difficulties experienced by students during the translating process.18 English Education students were taken as the sample of the study by purposive sampling. The students were given translation test which contained idiomatic expressions. The students’ translation results wereanalysed to know the accuracy level. The resultof accuracy level then leads to the analysis of students’ difficulties in translating idiomatic expressions. Therefore, questionnaire and short interview were employed to gain further data. The research found that 15% of students’ translations were totally inadequate, 23% were inadequate,10% were adequate, 14% were almost successful, and 38% were successful. The fact that the amount of the inaccurate translation result was more than the accurate translation result indicated that the students experienced difficulties during the translating process. Meanwhile, the translation difficulties experienced by students were lexical difficulty at 73%, stylistic difficulty at 67.5%, cultural difficulty at 66%, and 64% for grammatical difficulty. Based on the result, it is suggested for the students to improve their knowledge of English idiom and the translating ability. Inaddition, the students should optimize the use of dictionary to help produce good translation. For teachers, the result of the research can be used to reflect the students’ difficulties in translation, so that they are expected to overcome the difficulties by considering students’ ability and background knowledge in translation.